Revolutionizing plant stress response studies: developing a novel method for high-throughput analysis of multiple plant species - Boon, Chong Jun (Nanyang Technological University, 2023)
Studying transcriptomic changes in plants is crucial for the understanding of many plant biological processes. In this study, a method is proposed that aims to cheaply and efficiently multiplex RNA-seq libraries without the need of RNA barcoding, by using only conventional bioinformatical tools from typical RNA-seq analyses for demultiplexing. Arabidopsis thaliana, Brachypodium distachyon, and Oldenlandia corymbosa were chosen to create the multiplexed RNA sequence libraries in this study. Firstly, HISAT2 and Kallisto were compared for their ability to demultiplex the RNA libraries sequenced. HISAT2 was proven to be superior in de-multiplexing compared to Kallisto. HISAT2 also offered better optimisation capabilities. Secondly, it has been demonstrated that using O. corymbosa to spike transcripts can be used as a viable internal reference for count normalisation. Both methods have potential applications beyond plant stress research, which can offer cost savings and enhanced accuracy in RNA sequencing studies with a large sample quantity. Further optimisation of the demultiplexing process can also be achieved using HISAT2 parameters, allowing for more efficient and accurate RNA sequencing research.